Desenvolvimento de células solares fotoeletroquímicas utilizando nanopartículas de TiO2 e nanotubos de titanatos fotosensibilizados pela mesoporfirina - Souza, Antonio Paulo Santos (2014)
Since the development of the first dye sensitized solar cell in 1991, this field of research has grown considerably. TiO2 nanoparticles have been the main semiconductor on this kind of cell. With the advance in nanoscience and nanotechnology, new semiconductor structures with various morphological characteristics have been deeply studied for this sort of application. In this work, it was chosen to synthesize sodium titanate nanotubes (NTT-Na+) composed of Na2Ti3O7, by using anatase TiO2 associated with the hidrothermic method in high alkaline mean and titanate protonned nanotubes (NTT-H+) composed of H2Ti3O7 obtained by the washing of Na2Ti3O7 in 0,1mol/L HCl solution to perform the ionic trade, Na+ by H+. Both Na2Ti3O7 and H2Ti3O7 were used, as well as TiO2, on solar cell electrodes sensitized by mesoporfirin. In order to do that, some microscopy glass blades received the application of SnO2-F thin films by the use of the spray pyrolyse technique, acquiring conductive properties. After that, layers of TiO2, Na2Ti3O7 and H2Ti3O7 were deposited by using a glass stick over the conductive substrates, to work as support during the dye application. After the dye is adsorbed, the cells were closed using an electrolyte as redox pair (I3-/3I-) and conductive glass with layers of carbon in its surface, as counter electrode. The different samples of conductive glass showed electric resistance of 4,66 – 8,66 Ω/□. The layers of TiO2, Na2Ti3O7 and H2Ti3O7 over the conductive blades were analyzed through several microscopic techniques and presented, amongst others, porous characteristics with very irregular surfaces. While exposing the three photovoltaic devices to solar radiation of 1258 W/m², the following values of current and tension were verified: 13 μA and 370 mV for the cell with Na2Ti3O7 electrode; 7,6 μA and 256 mV for the cell with H2Ti3O7 electrode; 1,1 μA and 1,6 mV for the cell with TiO2 electrode.